Failure load of teeth restored by use of alumina copings: influence of residual tooth structure and cementation - Schmitter, Marc; Posavec, Tomislav; Müller, Denise; Mußotter, Katrin; Rammelsberg, Peter; Rues, Stefan (Dental materials journal, 2013)
To evaluate failure loads of teeth restored by use of alumina-coping, and to assess the effects of different amounts of residual tooth structure and different cements, standardized artificial alumina copings were fabricated on seventy-two molars. 24 of the copings were cemented by use of an adhesive resin cement (P-group), n=24 by use of glass-ionomer cement (K-group), and n=24 by use of a self-adhesive modified composite resin-cement (R-group). After artificial ageing (10,000 thermal-cycles between 6.5 and 60°C; 1,200,000 chewing cycles with Fmax=64 N), the specimens were loaded until failure (cross-head-speed: 0.5 mm/min). In the K-group 83% of the specimens failed during chewing simulation. Statistical analysis included chi-squared-test, unpaired-to-sample-t-test, and ANOVA. For severely damaged teeth, loads to failure in the P-group (384 N) were significantly (p=0.03) higher than in the R-group (295 N). For severely damaged teeth, use of composite resin cement resulted in higher loads to failure than use of other cements.
Gesehen am 12.07.2021